THE EFFECT OF PROBLEM-BASED LEARNING ASSISTED WITH PHET SIMULATION ON STUDENTS’ LEARNING OUTCOMES OF LIGHT AND OPTICAL DEVICES OPTICS TOPIC - Zahra, Fathia; Oktavia, Rani; Azhar, Aulia; Arif, Khairil; Sari, Monica Prima (Pendidikan IPA, FMIPA, UNP, 2024)
This research is based on the preliminary study conducted at SMPN 16 Padang which found that students' learning outcomes in science teaching are still considered suboptimal. This is indicated by several students' scores that have not yet met the Learning Outcome Completion Criteria of 80. This research aims to determine the effect of Problem-Based Learning (PBL) model assisted by PhET simulations on the learning outcomes of eighth-grade students at SMPN 16 Padang. The type of research is a quasi-experiment with a non-equivalent control group design. The population in this study is all the eighth-grade students of SMPN 16 Padang. Sample collection was conducted using purposive sampling techniques. Thus, the research samples were obtained from students in class VIII 2 and VIII 4. The research samples consisted of experimental class applying the Problem-Based Learning model assisted by PhET simulations and control class using the conventional learning model. Data collection was conducted through tests administered before (pretest) and after the treatment (posttest) on the experimental and control classes in the form of multiple-choice questions. The obtained data were analyzed using inferential statistical analysis, and the results of the two-sample t-test for the pre-test and N-gain were 0.002 for the pre-test significance and 0.000 for the N-Gain significance, which means was rejected or there was a significant difference between the two groups because the significance value (p) was less than 0.05. Thus, it can be concluded that there is a significant influence of the application of the PBL learning model assisted by PhET simulations on the learning outcomes of eighth-grade students in the subject of light and optical instruments.